Nutrient use in Leucaena leucocephala and cajanus cajan in maize/cassava alley cropping on Terre de barre, Benin Republic - Horst, Walter J.; Kuehne, R.; Kang, B. (1995)
On a Ferralic-haplic Acrisol (terre de barre non degradee) in Southern Benin Republic, four years after the establishment of the hedgerows, yields of maize and cassava alley cropped with Leucaena leucocephala and Cajanus cajan were no better than those in control plots without hedgerows. Reduced crop yields were mainly due to competition with the hedgerows for water and nutrients as Indicated by lower soil moisture and nitrogen-nitrogen concentration the soil solution and high root-Iength densities in plots with hedgerows. Nitrogen balance data showed that the benefit to the food crop from the N applied in prunings was limited in this trial. In the long-term the hedgerows may improve soil productivity by enhancing the build-up of organic C and N and reducing leaching of nutrients, thereby increasing the efficiency of utilization of soil and fertilizer nutrients.